The Influence of Kahoot Evaluation Tools on Student Learning Outcomes in Indonesian Language Subjects on Modern Poetry Text Material for Class VIII at Sinar Husni Middle School - Mutia Asmi Fadhillah; Budiman Budiman (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
The objective of this study was to determine the influence of the Kahoot application on students’ learning achievements in the Indonesian language subject of modern poetry text material for class VIII at SMP Sinar Husni. In this study, the researcher used a quantitative research method with an experimental research type with a quasi-experimental design. This type of research involves the application of a specific treatment or manipulation of an independent variable (X) to examine its causal effect on the dependent variable (Y). Quasi-experimental research is a type of research that aims to test the causal relationship between variables but does not use random assignments to form experimental and control groups. The results of this study clearly prove that the use of Kahoot evaluation media has a positive and significant effect on the learning outcomes of class VIII students at SMP Sinar Husni, especially on the material of modern poetry texts in Indonesian language lessons. A significant increase in the average posttest score in the experimental group using Kahoot, as well as support from the results of statistical tests (normality, homogeneity, and hypothesis testing), indicate that Kahoot is more effective than conventional evaluation methods. In addition, students’ positive responses to the use of Kahoot, as reflected in the results of the questionnaire, indicate that this platform is able to create a more interesting and motivating learning atmosphere. Therefore, Kahoot has proven to be an effective innovation in overcoming student boredom and encouraging increased learning outcomes on previously less popular materials.